Liberating Political Commitment Based on Democracy in General Election - Saimima, Johan Robert; S., Korneles Balak; Picauly, Jessyca Haniel; Kaihena, Ahustein J.; Sinaga, Rouli Retta Trifena (Sekolah Tinggi Teologi Intheos Surakarta, 2025)
The implementation of the General Election, including its implications for governance, has so far been full of various deviations from the principles of democracy. Therefore, with a theological perspective, democracy needs to be rebuilt to free society from democratic shifts in the Election and governance that have an impact on discomfort in living together. This article aims to construct a liberating political commitment of Christian society based on a dialogue between the ideas of democracy according to Karsadi and Franz Magnis-Suseno with the idea of the prophetic role of the church according to John Chr. Ruhulessin. The result of this study shows that a liberating political commitment can be built through the internalization of church teachings, so that the church is responsible for providing Christian political ethics education.